A novel method to quantify base substitution mutations at the 10−6 per bp level in DNA samples. (10th September 2017) - Yamashita, Satoshi; Iida, Naoko; Takeshima, Hideyuki; Hattori, Naoko; Maeda, Masahiro; Kishino, Takayoshi; Nagano, Reiko; Shimazu, Taichi; Tsugane, Shoichiro; Ushijima, Toshikazu
Abstract: Somatic base substitution mutations of frequencies at the 10 −6 /bp level are expected to be present in many biomedical samples, such as tissues exposed to carcinogenic factors and exhausted stem cells. However, measurement of such rare mutations has been very difficult in human DNA samples. Here, we invented the use of 100 copies of genomic DNA as a template for amplicon deep sequencing so that a real mutation in a single DNA molecule would be detected at a variant allele frequency of 1% while sequencing errors have less frequency. In addition, we selected 15, 552 error-resistant base positions whose mutation frequency was expected to reflect that of base positions that can drive carcinogenesis or potentially even of the entire genome. The validity of the method was first confirmed by the successful detection of mutations premixed at the frequency of 0.1%. Second, increasing mutation frequencies (4–60 × 10 −6 /bp) were successfully detected in cells treated with increasing doses of one of two mutagens, and their signature mutations were detected. The ratio of non-synonymous mutations to synonymous mutations time-dependently decreased after treatment with a mutagen, supporting the neutral theory of molecular evolution for somatic mutations. Importantly, gastric mucosae exposed to Helicobacter pylori infection was shown to have significantly higher mutation frequency than those without. These results demonstrated that our new method can be used to measure rare base substitution mutations at the 10 −6 /bp level, and is now ready for a wide range of applications. Highlights: A novel method to quantify mutations at the 10 −6 per bp level was established. The method can be applied to a wide range of mutation studies using human samples. Non-synonymous mutations in cells exposed to a mutagen were selected against.